Geopolitical Dynamics in The Golden Ocean by Patrick O’Brian - Çetin, Gülsüm Tuğçe (My University, 2024)
Literary works, as a medium for conveying cultural messages, play a pivotal role in both generating and disseminating political hegemony. The recent incorporation of critical geopolitics into literary criticism, originally an offshoot of international relations, signifies an expansion of its analytical purview to scrutinise literary works and expose latent political practices. At the core of critical geopolitics is the assertion that geopolitics is not an impartial framework but a socially, culturally, and politically constructed discourse designed to organise global politics. The methodology of critical geopolitics entails a meticulous examination and delineation of discourses that shape a specific mindset, adhering to particular understandings and objectives. This scrutiny of discourses unveils the intricate interplay between geopolitics and knowledge production, wherein specific political and cultural assumptions are unequivocally presented as universal truths. Thus, the resultant knowledge reflects not only the unique mindset of a particular subject and culture but also perpetuates the marginalisation of alternative perspectives. In essence, the knowledge generated within the realm of geopolitics, encompassing perceptions of place and identity, is inherently non-neutral; rather, it constitutes constructed representations. The discourses wielded in this construction process are subjective expressions strategically tailored to serve distinct objectives. This study endeavours to illustrate how meanings and power dynamics are intricately intertwined with these intentionally crafted representations in The Golden Ocean (1956) by Patrick O’Brian. Through this analysis, the study seeks to unravel the complex nexus between literature, geopolitical constructions, and the perpetuation of power relations.
Keywords: Discourse; Patrick O'Brian; The Golden Ocean; critical geopolitics